Desempenho técnico e econômico de forrageiras tropicais em sistema integrado de produção no cerrado de baixa altitude - Ferreira, João Paulo [UNESP] (2015)
Production systems that enable sustainability in agriculture as integration Crop-Livestock (ILP) and no-tillage (NT), as well as provide increased productivity, the full soil conservation. Thus, aimed in an Oxisol under irrigated conditions LATOSOL the Cerrado, to evaluate: 1) the productive performance and the chemical quality of the silage produced in different production systems; 2) the components of the production and productivity of maize in consortium in different spacing and the remaining forage; 3) to evaluate every autumn cut the spring, forage yield and its chemical composition after harvest of silage; 4) in the last cut, check beyond the forage yield, macronutrient contents and the decomposition of straw fodder after desiccation in the spring and its effect on soybean crop; 5) while driving in production systems, changes in chemical properties and density in the layer 0 to 0,10 and from 0,10 to 0,20 m at the end of each production cycle, in addition to the determination of stock carbon; 6) the ILP's economic performance under no till during the study period, in order to verify the sustainability and profitability of each system. It was found that for grain yield or silage moisture grains recommendes to the consortium of corn with Xaraés grass, whether in row spacing of 0,90 or 0,45 m. For the production of the whole plant silage, it is recommended consortium with corn Tanzaniagrass. The variation in time to harvest corn for silage or grain production did not affect the production or chemical composition of Xaraés and Tanzania grasses set out in consortium with corn. Nitrogen fertilization of forage after the consortium with corn not reflected in an increase in dry matter production and nutritional and chemical composition of grasses in area under nine years in no-tillage system. In irrigated conditions in the Cerrado, aiming increasing soybean yield in succession to tropical forages, ...